2018
DOI: 10.1111/jcmm.13675
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA ABHD11‐AS1 promotes the development of endometrial carcinoma by targeting cyclin D1

Abstract: To investigate the expression, role and mechanism of action of long non‐coding RNA (lncRNA) ABHD11‐AS1 in endometrial carcinoma. The expression of lncRNA ABHD11‐AS1 was quantified by qRT‐PCR in human endometrial carcinoma (n = 89) and normal endometrial tissues (n = 27). LncRNA ABHD11‐AS1 was stably overexpressed or knocked‐down in endometrial carcinoma cell lines to examine the cellular phenotype and expression of related molecules. Compared to normal endometrial tissue, lncRNA ABHD11‐AS1 was significantly ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…We 19 and others have shown that lncRNAs can directly interact with key signaling proteins to regulate their function. It was reported that lncRNA ABHD11-AS1 38 interacted with Cyclin D1 and promoted the growth of endometrial cancer cells, but the mechanism was unclear. LncRNA was also shown to regulate the transcription of CCND1 39 .…”
Section: Discussionmentioning
confidence: 99%
“…We 19 and others have shown that lncRNAs can directly interact with key signaling proteins to regulate their function. It was reported that lncRNA ABHD11-AS1 38 interacted with Cyclin D1 and promoted the growth of endometrial cancer cells, but the mechanism was unclear. LncRNA was also shown to regulate the transcription of CCND1 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin D1 is an important mediator of cancer initiation, development, and metastasis and is associated with poor prognosis. LncRNA ABHD11-AS1 promotes the development of endometrial carcinoma by targeting cyclin D1[ 26 ]. Interfering with cyclin D1 leads to PI3K/Akt signal suppression [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…SNHG5 promotes CRC cell survival by counteracting STAU1-mediated mRNA destabilization [25]. LncRNA ABHD11 Antisense RNA 1 (ABHD11-AS1) has been identified to act as diagnostic and prognostic bio-markers as well as therapeutic target in endometrial carcinoma, ovarian cancer, bladder cancer, gastric cancer [7–10]. However, the roles and underlying mechanisms of ABHD11-AS1 was unknown in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA ABHD11 antisense RNA 1 (ABHD11-AS1), locating at the human chromosome 7 q11.23, has been identified as one oncogene in various cancer [7–10]. For instance, Liu et al demonstrated that lncRNA ABHD11-AS1 stimulates cell proliferation and invasion of endometrial carcinoma [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation